A la recherche de la ressource foncière territoriale sur les territoires de montagne - Catherine Herrera (Revue de Géographie Alpine)
Land and property issues constitute a crucial element in spatial planning and management. Spatial malfunctions (homogenisation of landscapes, urban sprawl, etc.) and socio-economic problems (exclusion of the most fragile elements of the population, growth of second homes, etc.) have led local authorities in charge of managing land and development to re-examine their relationship with space. The rhetoric of political actors responsible for addressing this question has thus become increasingly marked by a desire to intervene more strongly in land management issues. However, they have always come up against the problem of deciding how to deal with privately owned land, which constitutes a substantial part of their territories//the area under their control. The question of management at a level above that of the commune (supra-communal) is thus envisaged in order to avoid a public/private dialectic by promoting the idea of a territorial land resource. The processes involved in this step could thus be seen as a means of clarifying the methods of land management at the scale of a supra-communal territory through better knowledge and application of regulations, the basis for any measure of collective action.